Herbal drugs and drug interactions [Bitkisel ilaçlar ve ilaç etkileşmeleri] - (:unkn) unknown (My University, 2012)
Herbal drugs are defined as any form of a plant or plant product that contains a single herb or combinations of herbs that are believed to have complementary effects. Although they are considered to be safe, because they are natural, they may have various adverse effects, and may interact with other herbal products or conventional drugs. These interactions are especially important for drugs with narrow therapeutic indices. In the present study, pharmacokinetic and pharmacodynamic interactions of some most commanly used herbals (St John's wort, ginkgo biloba, ginseng, ginger, garlic, echinacea, ephedra and valerian) with the conventional drugs were reviewed. Pharmacokinetic interactions involve mainly induction or inhibition of the cytochrome P450 isozymes and p-glycoproteins by the herbal medicine, thus changing the absorption and/or elimination rate and consequently the efficacy of the concommitantly used drugs. St John's wort, a well known enzyme inducer, decreases the efficacy of most of the other drugs that are known to be the substrates of these enzymes. Pharmacodynamic interactions may be due to additive or synergistic effects which results in enhanced effect or toxicity, or herbal medicines with antagonistic properties reduce drug efficacy and result in therapeutic failure. For exampla, St John's wort may have synergistic effects with other antidepressant drugs used by the patient, resulting in increased CNS effects. Herbals like ginseng, ginkgo, garlic, ginger were reported to increase bleeding time, thus potentiating the effect of anticoagulant and antithrombotic agents. In conclusion, patients should be warned against the interaction between the herbal products and conventional medicines.
Keywords: Garlic; Ginger; Ginkgo; Ginseng; StJohn's wort